Purification and Partial Characterization of Protease from Biduri (Calotropis gigantea) Latex - Yuli Witono; Aulanni’am .; Simon Bambang Widjanarko (Jurnal Teknologi dan Industri Pangan, 2007)
The main objectives of this research we to purify protease from biduri (Calotropis gigantean) latex and its partial characterization in relation with this application in the food processing. Protease was extracted from biduri latex by using ammonium sulphate 35-80%, dialyzed and then purified subsequently through sephadex G-25 gel and CM sephadex C-50 caution exchanger. Biduri protease has specific activity of 59 unit/g in casein substrate. Optimum pH was 7 and temperature 550C. Apparent Km was 21.63 g/ml and reaction maximum velocity (Vmax) being 18.9 mg/ml/min. SDS-PAGE (Sodium Dodecyl Sulfate-Polyacrylamide Gel Electrophoresis) analysis showed the apparent molecular weight of the protease was 25.2 kD. Moreover, the protease can be inactivated at 900C for 10 min, or 600C for 30 min. Key Word : biduri (Calotropis gigantea), protease, purification, characterization.